Sudden Unexplained Death in Treated Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The overall incidence of sudden unexplained death in persons with epilepsy (SUDEP) was measured, and subgroups with a high risk of SUDEP were identified among a cohort of 6,044 persons aged 15-49 years listed in the Saskatchewan Health prescription drug file.